2019
DOI: 10.1080/17445302.2019.1612544
|View full text |Cite
|
Sign up to set email alerts
|

Ship energy performance study of three wind-assisted ship propulsion technologies including a parametric study of the Flettner rotor technology

Abstract: A 4 degrees of freedom ship performance prediction model is used to compare wind-assisted ship propulsion technologies: the Flettner rotor, a wingsail and the DynaRig concept. An Aframax Oil Tanker on a route between Gabon and Canada is used in a case study to compare the three technologies using actual information for the voyage. The fuel savings for were calculated and they varied between 5.6% and 8.9%; the Flettner rotor showed the largest fuel savings. A parametric study of the Flettner rotor technology wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
35
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(39 citation statements)
references
References 9 publications
3
35
1
Order By: Relevance
“…When modeling the performance of ships with WASP technologies, more sophisticated models that account for side forces and yaw moments should be used to obtain more accurate fuel consumption predictions [71]. Many of the studies use reconstructed routes from AIS data and/or shortest paths [6,7,68]. Ref.…”
Section: Environmental Factorsmentioning
confidence: 99%
See 3 more Smart Citations
“…When modeling the performance of ships with WASP technologies, more sophisticated models that account for side forces and yaw moments should be used to obtain more accurate fuel consumption predictions [71]. Many of the studies use reconstructed routes from AIS data and/or shortest paths [6,7,68]. Ref.…”
Section: Environmental Factorsmentioning
confidence: 99%
“…[42] found that fuel saving in the western coast of Europe, South China Sea, the Indian Ocean, and the Arabian Sea are the largest, while the fuel saving is the smallest in the Mediterranean Sea and off the west coast of Africa. Other studies also suggest that in different trading areas, significantly different fuel savings are found [6,7,68]. Last but not least, shipping companies could face risks associated to cargo-handling operations-such as potential damage to the technology [9]-hindering them from calling at specific ports with improper infrastructure [73].…”
Section: On-board and Commercial Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, from a practical point of view the sail area of the wing sail is twelve times bigger than the Flettner rotor; thus, the comparison is not determinant. Further research from [16] simulated two different routes for a tanker ship and compared the fuel savings when Flettner rotors or wing sails were installed onboard as wind-assisted propulsion systems. The result of the study showed that fuel savings using Flettner rotors are slightly higher than using wing sails (0.1-0.4% higher), even considering the power required to spin the rotors.…”
Section: Flettner Rotors Versus Wing Sailsmentioning
confidence: 99%